CALCULATION OF TARGET RELIABILITY SAIDI FOR DISTRIBUTION LINES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
In modern distribution lines reliability indicators are attached great importance. In regulations of the Russian Federation indicated the reliability indicators, which must be counted by Grid Company. SAIDI is one of them. In this article you can see the author's calculation of reliability indicator SAIDI for the distribution lines. Also there are an example of this calculation and comparing with the real measure, which we have taken from software complex «Accident».